Nanoscale processing of polyaniline and phthalocyanines for sensing applications - Zucolotto, V; Ferreira, M.; Cordeiro, M. R.; Constantino, CJL; Moreira, W. C.; Oliveira, O. N. (Elsevier B.V., 2006)
Nanostructured polyaniline-modified electrodes were fabricated via the electrostatic layer-by-layer (LbL) technique where polyaniline (PANI) was assembled with one of three tetrasulfonated metallic phthalocyanines, viz. iron (FeTsPc), nickel (NiTsPc) and copper (CuTsPc). The multilayer formation was monitored via UV-vis spectroscopy by measuring the increase in the 800 run absorption band due to PANI. Infrared spectroscopy in the transmission mode suggested specific interactions between PANI and the phthalocyanines, such as those between SO3- groups from the phthalocyanines and the protonated NH group from PANI. The films were employed to detect dopamine (DA) using cyclic voltammetry. In the presence of dopamine the PANI-based LbL films showed additional redox peaks at ca. 230 and 190 mV the oxidation peak increased linearly with the concentration of DA in the electrolytic solution. Films comprising PANI/FeTsPc were able to distinguish between DA and ascorbic acid (AA), which acts as a natural interferent in biological fluids. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: nanostructured layer-by-layer films; polyaniline-modified electrodes; phthalocyanines; dopamine sensor